A modified vertical muscle transposition for the treatment of large-angle esotropia due to sixth nerve palsy. (3rd July 2018) - Sabermoghadam, Aliakbar; Etezad Razavi, Mohammad; Sharifi, Mohammad; Kiarudi, Mohammad Yaser; Ghafarian, Sadegh
ABSTRACT: Introduction : Multiple different procedures have been proposed to address complete sixth nerve palsy with severe abduction limitation. In this study, we report a modification of the Hummelsheim's procedure. It is in fact muscle pulley transposition that obviates the need for tenotomy or muscle splitting. For the first time, Muraki and Nishida proposed this technique. Materials and Methods : Patients with large angle esotropia and abduction limitation of minus four or greater were enrolled. The surgery involved insertion of a polyester monofilament fiber suture through the temporal muscular margin of each vertical rectus muscle at approximately one-third of the width from the edge at 10 mm behind the muscle insertion. We tried to insert sutures away from the vessels of vertical muscles. Then, the vertical muscles were transposed without any tenotomy or splitting and the sutures were secured to the sclera 16 mm from the limbus in supratemporal and infratemporal quadrants. In all of the patients, this transposition was combined with medial rectus recession. Results : A total of 10 patients were included; all of them had an esotropia with profound abduction deficit (−4 or more). The mean age of patients was 44.2 ± 9.2 years (mean ± standard deviation) (range: 28–57). The mean preoperative deviation was 49.5 ± 9 PD prism diopters (PD) (range: 40–65 PD). The mean preoperative abduction limitation was −4.8 ± 0.8. The patients were followed for at least 6 months. Postoperative deviation ranged from orthotropia to 12 PD of esotropia and all the patients obtained abduction at least beyond the midline. No vertical ductional disturbances or deviations were developed. The adduction was not compromised in any patient. Anterior segment ischemia did not occur in any patients. Conclusion : This procedure is comparable to traditional procedures with the advantages of no need to tenotomy or splitting and can be a good alternative to conventional Hummelsheim's procedure.